2014
DOI: 10.1007/s00198-014-2656-y
|View full text |Cite
|
Sign up to set email alerts
|

The biomaterial-mediated healing of critical size bone defects in the ovariectomized rat

Abstract: Due to the similarities between the osteoporotic animal model and the human condition of postmenopausal osteoporosis, it might be relevant to consider the potential clinical implication of the osteoporotic condition in the biomaterial-mediated bone tissue healing/regeneration process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…The ovariectomized rat model is a widely used model to evaluate the efficacy of new drug entities to prevent or treat postmenopausal osteoporosis. Surgical ovariectomy results in a state of high bone turnover and rapid bone loss, which have many similarities between the phenotypes observed in OVX rats and humans [20]. Here, we found that ovariectomy significantly increased serum ALP and OCN, as well as serum CTX and urinary HOP compared with the sham rats.…”
Section: Discussionsupporting
confidence: 59%
“…The ovariectomized rat model is a widely used model to evaluate the efficacy of new drug entities to prevent or treat postmenopausal osteoporosis. Surgical ovariectomy results in a state of high bone turnover and rapid bone loss, which have many similarities between the phenotypes observed in OVX rats and humans [20]. Here, we found that ovariectomy significantly increased serum ALP and OCN, as well as serum CTX and urinary HOP compared with the sham rats.…”
Section: Discussionsupporting
confidence: 59%
“…25 After 12 weeks, imperatorin (Solarbio) or normal saline (NS) was administered. Thirty 3-month-old SD male rats were procured from Shanghai Laboratory Animal Center (Shanghai, China).…”
Section: Experimental Animals and Treatmentmentioning
confidence: 99%
“…After 1 week of adaptation, ten rats were subject to sham operation and the remaining rats underwent bilateral ovariectomy (OVX) as per protocol previously reported. 25 After 12 weeks, imperatorin (Solarbio) or normal saline (NS) was administered. Further, the rats were divided into three groups (N = 10/group): SHAM group which underwent sham operation received NS (50 mL/kg/d) by gavage; OVX group which underwent bilateral ovariectomy also received (50 mL/kg/d) NS by gavage; whereas, the other ovariectomy group, IMP received imperatorin (20 mg/kg/d) by gavage.…”
Section: Experimental Animals and Treatmentmentioning
confidence: 99%
“…To date, few biomaterials have been investigated in the repair of OP calvarial defects. For instance, Lin and coworkers found enhanced OP bone regeneration by strontium-substituted calcium silicate bioactive ceramics [18]; another report from Durão and colleagues showed that the implantation of a biocompatible Bovine-Bone Mineral (BBM) graft could heal critical-size calvarial defects in ovariectomized (OVX) rats [19]. However, it was unknown whether ASCs could contribute to the repair of critical-size OP calvarial defects.…”
Section: Introductionmentioning
confidence: 99%